1987
DOI: 10.2118/14479-pa
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Engineering in Coal Seams: Part 2—Observations of Gas Movement in Coal Seams

Abstract: Summary This paper, the second of two concerning the movement of gas in coal seams, covers observations of seam fluid pressures and flows in mines in northern and central Queensland, Australia. Techniques based primarily on underground measurement rather than measurements from surface primarily on underground measurement rather than measurements from surface boreholes were used to gain information on the seams. The techniques used for in-seam studies are described because they differ substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 0 publications
0
9
0
3
Order By: Relevance
“…The coals within these basins are of significant interest for coal seam gas exploration and production, particularly within the “Walloon Fairway” (Figure ). Viability of coal seam gas production is partially dependent on the intersection of production wellbores to reservoir (coal seam) fracture and cleat permeability, whereas primary porosity plays a diminished role [ Gray , , ]. Furthermore, the ability of these fractures and cleats to transmit fluid is partially in situ stress dependent, with fractures that are critically stressed being more likely to be effective fluid conduits than those that are not [ Barton et al ., ; Zoback , ].…”
Section: Introductionmentioning
confidence: 99%
“…The coals within these basins are of significant interest for coal seam gas exploration and production, particularly within the “Walloon Fairway” (Figure ). Viability of coal seam gas production is partially dependent on the intersection of production wellbores to reservoir (coal seam) fracture and cleat permeability, whereas primary porosity plays a diminished role [ Gray , , ]. Furthermore, the ability of these fractures and cleats to transmit fluid is partially in situ stress dependent, with fractures that are critically stressed being more likely to be effective fluid conduits than those that are not [ Barton et al ., ; Zoback , ].…”
Section: Introductionmentioning
confidence: 99%
“…众所周知, 煤层气割理-裂隙系统中充满水 [17][18][19] , 但是关于煤基质孔隙中是否存在水, 若存在水的分 布如何却存在争议. 在澄清煤储层的孔隙分类的基 础上, 为了判别煤层解吸气在不同尺寸基质孔隙中 的运移方式, 仍需研究煤储层的原始气水分布.…”
Section: 煤储层原位气水分布特征unclassified
“…Based on these validation studies, the gas emission curves were modified to eliminate the observed over-and underestimates of emissions and produced the British Coal Firedamp Prediction Method as it is known today. Building upon the understanding of how a longwall panel and the surrounding strata respond to progressive coal extraction, gas emission patterns associated with conventional mechanised longwall mining have been extensively studied in the past few decades (Barker Read and Radchenko, 1989;Durucan, 1981;Gray, 1987;Karacan et al, 2011;Lunarzewski, 1998;Noack, 1998). Whittaker (1974) described dynamic stress changes and the formation of stress abutments in a longwall panel ahead of an advancing longwall coal face.…”
Section: Introductionmentioning
confidence: 99%